Cxxc Finger Protein 1 Positively Regulates GM-CSF-Derived Macrophage Phagocytosis Through Csf2rα-Mediated Signaling - Hui, Zhaoyuan; Zhou, Lina; Xue, Zhonghui; Zhou, Lingfeng; Luo, Yikai; Lin, Feng; Liu, Xia; Hong, Shenghui; Li, Wei; Wang, Di; Lu, Linrong; Wang, Jianli; et al. (Frontiers in Immunology, 2018)
Macrophages have a defensive function against bacteria through phagocytosis and the secretion of cytokines. Histone modifications play an essential role in macrophage func-tions. Here, we report that Cxxc finger protein 1 (CFP1), a key component of the SETD1 histone methyltransferase complex, promoted the phagocytic and bactericidal activity of GM-CSF-derived macrophages. CFP1-deficient mice were more susceptible to bacterial infection due to the decreased expression of Csf2rα, a subunit of the GM-CSF receptor essential for inflammation and alveolar macrophage development, through the loss of H3K4 modiﬁcations in the promoter of the Csf2rα gene. In addition, the lung tissues of CFP1-deficient mice exhibited spontaneous inflammatory symptoms, including both the infiltration of inflammatory cells and the accumulation of surfactant phospholipids and proteins. Furthermore, we showed that Csf2rα and PU.1 can partially rescue the defects in phagocytosis and in the intracellular killing of bacteria. Collectively, our data highlight the importance of CFP1 in the phagocytic and bactericidal activity of macrophages.